Selective Prevention for Anxiety and Resilience Promotion: Outcomes of an Anxiety Prevention and Resilience Program with Girls at Risk - Gallegos Guajardo, Julia; Ruvalcaba Romero, Norma A.; Langley, Audra; Villegas Guinea, Diana (Pensando Psicología, 2015)
Introduction: Research has shown that the number of children and adolescents experiencing emotional difficulties such as anxiety is escalating, especially for those groups at risk. Living in an orphanage has been considered a risk factor for delays in an individuals’ social, emotional and behavioral development.Objective: The aim of this study was to evaluate the effectiveness of the Spanish version of the FRIENDS program, a CBT-based resilience program, with 57 girls from low socioeconomic status (SES) background that were living in an orphanage.Method: Participants received the program for 10 consecutive weeks, and pre- and post-test measures were collected.  Measures evaluated participants’ anxiety symptoms, level of self-concept, hope, coping skills, and psychosocial difficulties. Social validity was also assessed.Results: Results showed positive changes, including a decrease in anxiety symptoms and psychosocial difficulties, as well as an increase in their proactive coping skills. Several subscales and items of the self-concept and hope outcome measures also reported statistically significant improvements.Conclusions: Participants and parents/caregivers reported that the program was both enjoyable and useful. Implications of the findings and directions for further research are discussed.
Keywords: anxiety; cognitivebehavior program; orphanage resilience; prevention